2015
DOI: 10.1037/a0038402
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of change in youth anxiety during cognitive—behavior therapy.

Abstract: Objective To evaluate changes in the trajectory of youth anxiety following the introduction of specific cognitive behavior therapy (CBT) components: relaxation training, cognitive restructuring, and exposure tasks. Methods 488 youths ages 7–17 years (50% female; 74% ≤ 12 years) were randomly assigned to receive either CBT, sertraline (SRT), their combination (COMB), or pill placebo (PBO) as part of their participation in the Child/Adolescent Anxiety Multimodal Study (CAMS). Youths in the CBT conditions were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
87
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 154 publications
(95 citation statements)
references
References 42 publications
(66 reference statements)
6
87
1
1
Order By: Relevance
“…cognitive restructuring, relaxation, psychoeducation). However, we note that research has found that early introduction of exposures is associated with positive outcomes (Gryczkowski et al, 2013) and the entry of exposure into typical CBT has shown to be followed by a significant acceleration in the rate of progress in treatment (even after other treatment techniques are introduced; Peris et al, 2015). In other words, exposure has evidenced unique contributions to outcome (Voort et al, 2010).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…cognitive restructuring, relaxation, psychoeducation). However, we note that research has found that early introduction of exposures is associated with positive outcomes (Gryczkowski et al, 2013) and the entry of exposure into typical CBT has shown to be followed by a significant acceleration in the rate of progress in treatment (even after other treatment techniques are introduced; Peris et al, 2015). In other words, exposure has evidenced unique contributions to outcome (Voort et al, 2010).…”
Section: Discussionmentioning
confidence: 83%
“…Although particular aspects of CBT for various anxiety disorders in youth vary by treatment manual, exposure is a core element across specific interventions. Exposure is perhaps the most integral component of CBT, influencing the trajectory of improvement (Peris et al, 2015), predictive of treatment outcome (e.g., Voort, Svecova, Jacobsen, & Whiteside, 2010), and showing comparable performance when conducted in isolation and compared to more comprehensive CBT interventions (e.g., Deacon & Abramowitz, 2004). Additionally, exposure as a therapeutic tool is strengthened by its versatility, capable of being conducted across varied settings and tailored to individual presentations (Peterman, Read, Wei, & Kendall, 2014).…”
mentioning
confidence: 99%
“…Such research can include more frequent assessment and more sophisticated and dynamic modeling (e.g. Peris et al, 2015) of factors that hinder and facilitate emotional processing. It will be especially important to map the temporal sequencing of components of unproductive and productive processing over time and to identify the factors that predict change in PTSD-specific symptoms.…”
Section: Clinical Implications and Conclusionmentioning
confidence: 99%
“…Cognitive-behavioral therapy (CBT) is a proven and efficacious treatment for anxiety demonstrating durable effects over time (Benjamin, Harrison, Settipani, Brodman, & Kendall, 2013; Ginsburg et al, 2014; Higa-McMillan, Francis, Rith-Najarian, & Chorpita, 2016). Use of exposure, or confronting fear stimuli within the context of CBT, is the key ingredient of intervention leading to improved outcomes (Kendall et al, 2006; Peris et al, 2015). Despite scientific recognition that exposure is critical to the success of CBT for anxiety, recent estimates suggest that only 10–30 percent of clinicians endorse using exposure therapy in routine clinical care (Becker, Zayfert, & Anderson, 2004; Borntrager, Chorpita, Higa-McMillan, Daleiden, & Starace, 2013; Trask, Fawley-King, Garland, & Aarons, 2016; Whiteside, Deacon, Benito, & Stewart, 2016; Wolitzky-Taylor, Zimmermann, Arch, De Guzman, & Lagomasino, 2015).…”
Section: Introductionmentioning
confidence: 99%